INCREASING THE KNOWLEDGE OF TASIWALIE VILLAGE COMMUNITIES ABOUT SHARIA BANKS IN INDONESIA THROUGH SHARIA BANKING SOCIALIZATION - Arwin, Arwin; Sutrisno, Sutrisno; Hamka, Resky Amalia (Al-Mulk: Jurnal Pengabdian Masyarakat, 2023)
Collecting funds from the public and channeling them back to the community is a general banking activity, both conventional and Islamic banks. However, there is a fundamental difference, namely that Islamic banks not only focus on profit-oriented, but they also precipitate elements of benefit, for example carrying out social services such as qardh funds, infaq, zakat or other social services that are considered for the benefit of advantage. Tasiwalie Village, one of the villages in the Suppa sub-district, Pinrang Regency, is predominantly Muslim but generally uses conventional financial services. This is due to the need for more public knowledge about products at Islamic Banks. Community service needs to be carried out to increase the knowledge of the Tasiwalie Village community about Sharia banking which can be done through sharia banking outreach activities. This activity was carried out in 3 stages: planning, implementation and evaluation. This activity ran smoothly and was well received by community leaders and local residents.Keywords: Knowledge; Socialization; Sharia Banking.